Morbillivirus-associated lipid pneumonia in Arctic foxes. (November 2018) - Stimmelmayr, Raphaela; Rotstein, David S.; Maboni, Grazieli; Person, Brian T.; Sanchez, Susan
We describe lipid pneumonia in 5 of 24 Arctic foxes ( Vulpes lagopus ) in association with morbillivirus infection, and lymphoid depletion in 3 of these 5 foxes. Canine distemper virus (CDV) immunohistochemistry yielded positive staining in lung, lymph nodes, spleen, adipose tissue, and renal pelvic urothelial cells in 5 cases. Liver and bone marrow samples collected from these cases tested positive for morbillivirus by reverse-transcription PCR assay. Strains belonged to the CDV Arctic lineage based on sequencing of the hemagglutinin gene followed by phylogenetic analysis. Phylogenetic analysis of the phosphoprotein gene showed that the identified CDV strains were not closely related to any previously documented strains responsible for outbreaks in different animals in other parts of the world.